The Application of Practice Rehearsal Pairs (PRP) Method to Develop Inquisitiveness of Learning in Students - Aprilia Utami, N; Mustadi, A (KnE Social Sciences, 2019)
This study is a Classroom Action Research (CAR) conducted in two cycles. This study aims to increase the Inquisitiveness through the Practice Rehearsal Pairs (prp) method. Subject of this study consist of 40 students from science education course in Elementary School Teacher Education Department, Yogyakarta state university. Data collection techniques used in this study is questionnaires and observations. The data analysis technique used in this study are descriptive quantitative and calculates n-gain. The results of this study show that the application of learning using Practice Rehearsal Pairs (PRP) method is able to enhance students’ Inquisitiveness. It is proved by the increase in each cycle. From the results of the initial condition data, the students’ inquisitive obtained by questionnaire is 64.8, indicates as ”Fair” with 55% of the classical percentage. At the first cycle, it keeps going up subsequently to reach 67.3, indicated as “Good” with 60% of classical percentage. Then at the second cycle, it continues to rise to 69.7, categorized as “Good” with 67% of classical percentage. The results of the initial condition data, the students’ inquisitive obtained by observations is 64.3, indicates as ”Fair” with 55% of the classical percentage. At the first cycle, it keeps going up subsequently to reach 66.8, indicated as “Good” with 59% of classical percentage. Then at the second cycle, it continues to rise to 68.9, categorized as “Good” with 65% of classical percentage. Besides, the increase of students’ curiosity before and after the action can be seen from the normalized gain test from the pre-cycle questionnaire to the first cycle which reaches 0.071, indicated as ”low” category while from the pre-cycle questionnaire to the second cycle reaches 0.139, indicated as ”low” category. Furthermore, the gain value of observations from pre-cycle to the first cycle reaches 0.070 which is categorized as ”low” while the value of pre-cycle observations up to the second cycle reaches 0.116 which is categorized as ”low”. From the results and explanation, it can be concluded that the Practice Rehearsal Pairs (PRP) method can increase the Inquisitiveness of students in the ”science education” course. The purpose of this study is to improve the students’ inquisitiveness of learning Science. The subjects of the study were 40 students of Pendidikan Guru Sekolah Dasar or Primary Teacher Education at Yogyakarta State University. The students were cohort C, academic year 2017/2018 who were in their second semester. The study used Classroom Action Research (CAR) for the design and Practice-Rehearsal-Pairs (PRP) Method was used in this study. The data was gathered from classroom observation and questionnaire. The data was analyzed in descriptively and calculated twice. Each calculation was conducted after three meetings. This paper describes and discusses the results of the classroom observation and questionnaire. The talk will be closed by discussing the implications of the study. Keywords: Practice Rehearsal Pairs (PRP) method, Inquisitiveness, science education